GROWTH AND MODELLING OF InGaP NANOWIRES BY MBE - Fakhr, Ahmed (My University, 2013)
The growth of ternary InGaP nanowires (NWs) is explored. Free-standing NWs are grown with the Au nanoparticle-assisted method using a gas source molecular beam epitaxy (GS-MBE) system. The grown samples were characterized using scanning electron microscopy (SEM), transmission electron microscopy (TEM) and energy dispersive x-ray spectroscopy (EDX). These characterization techniques were employed to examine the composition of the InGaP NWs, the morphology and the crystal structure. With varying the growth conditions, such as temperature, growth rate and V/III flux, a dependence of the NWs' composition, morphology and crystal structure were observed. In addition, the characteristics of the NWs showed great dependence on the diameter of the Au seed particle responsible for the NW growth.
A physical-based growth model is developed to understand the NW growth results. The model deals with each of the group-III growth species differently and splits the group-V into two components, with each component associated with one of the group-III species. The model is able to match composition and morphology results obtained from the experimental data.
Furthermore, a nucleation-based model is employed and integrated with the growth model to predict the crystal structure of the NWs. Based on this model, the operating regions for all out samples were illustrated. In addition, the dependence of the crystal structure of the NWs on the Au seed diameter, in our samples, was attributed to the change in the surface energies of the formed nucleus as the Au seed diameter change.
Keywords: nanowires; InGaP; Ternary; Model; composition; staching faults; Nanotechnology fabrication; Nanotechnology fabrication